2005
DOI: 10.1080/08111470500354216
|View full text |Cite
|
Sign up to set email alerts
|

“Danger lurks around every corner”: Fear of Crime and its Impact on Opportunities for Social Interaction in Stigmatised Australian Suburbs

Abstract: This article examines some of the ways in which fear of crime impacts upon opportunities for social interaction among residents in stigmatised suburbs. As we explore in this article, neighbourhoods that are stigmatised by virtue of material disadvantage and poor reputations tend to be associated with a number of social problems, including higher rates of crime. This association with crime, our research suggests, has an impact on social interaction in these neighbourhoods. Specifically, fear of crime may make p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 41 publications
4
49
1
1
Order By: Relevance
“…Instead young people are often seen as a danger to common values surrounding property maintenance, noise and privacy (Bostrom, 2001). This is even more pronounced for young people in public housing (Arthurson, 2004;Palmer et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Instead young people are often seen as a danger to common values surrounding property maintenance, noise and privacy (Bostrom, 2001). This is even more pronounced for young people in public housing (Arthurson, 2004;Palmer et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…However, 'normal' home occupiers can deny the domestic competence of perceived outsiders who are often seen as incapable tenants (Palmer et al, 2005). Thus, proving competence can be seen as a way of attaining access to, and partial ownership of, the 'normal' home occupying discourse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Jackson (2005) found that perceptions of incivilities affect perceptions of community cohesion, perceived likelihood of crime and the frequency of worry about crime, suggesting the inability of the individual to manage the risk of criminal victimisation and its consequences is one of the reasons individuals worry. Based on qualitative research in neighbourhoods in Adelaide, Palmer et al (2005) noted how in stigmatised neighbourhoods with high rates of incivilities, fear of crime may restrict social interaction and trust. This relationship may be 'self-reinforcing': perceptions of increasing incivilities increase fear of crime, which in turn reduces social interaction and organisation and further increases incivilities.…”
Section: Incivilitiesmentioning
confidence: 99%
“…4 Research indicates that feeling unsafe in one's neighborhood and the fear of being a victim of crime can decrease social ties and social cohesion among neighbors. [5][6][7][8][9][10] Further, perceived neighborhood violence and hearing about violence in one's community, in addition to being a victim of violence, contributes to adverse psychological conditions such as anxiety, depression and stress. 11,12 For that past 3 decades, a common approach to addressing the health of disadvantaged communities has been establishing community coalitions.…”
Section: Introductionmentioning
confidence: 99%